Revisão integrativa dos processos de manipulação de alimentos seguida pela elaboração de um curso em boas práticas na manipulação de alimentos em ambiente virtual de aprendizagem - Dallacqua , Aparecida (2021)
The course on good practices in food handling, in addition to being a requirement of health legislation in Brazil, is an essential and effective tool for the production of safe food, thus avoiding Foodborne Diseases (DTA), which are considered by the UN the biggest public health problem in the world. This work consists of elaborating learning objects to create courses of good practices in food handling in a virtual learning environment. The final objective of the course is to train and change the habits of the handlers in order to minimize the risks in food production. To contemplate all food handlers who need to participate in this type of training, bibliographic research will be carried out to outline a profile of these handlers, in different regions of the country. With these data and based on Richard Mayer's Multimedia learning theories, meaningful and contextualized learning, as well as in cyberogy, a Course on Good Practices in Food Handling will be designed in a virtual learning environment (VLE). The course will be freely accessible and will consist of video lessons, podcast, Manual of Good Practices and complementary booklets. To better meet everyone's needs, learning styles will also be considered, such as the Felder-Silverman model. And for the design of the course itself, the 4C / ID instructional design model was used as a basis.